If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 1)(5x + 2) = 0 Reorder the terms: x(1 + x)(5x + 2) = 0 Reorder the terms: x(1 + x)(2 + 5x) = 0 Multiply (1 + x) * (2 + 5x) x(1(2 + 5x) + x(2 + 5x)) = 0 x((2 * 1 + 5x * 1) + x(2 + 5x)) = 0 x((2 + 5x) + x(2 + 5x)) = 0 x(2 + 5x + (2 * x + 5x * x)) = 0 x(2 + 5x + (2x + 5x2)) = 0 Combine like terms: 5x + 2x = 7x x(2 + 7x + 5x2) = 0 (2 * x + 7x * x + 5x2 * x) = 0 (2x + 7x2 + 5x3) = 0 Solving 2x + 7x2 + 5x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(2 + 7x + 5x2) = 0 Factor a trinomial. x((1 + x)(2 + 5x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Subproblem 3
Set the factor '(2 + 5x)' equal to zero and attempt to solve: Simplifying 2 + 5x = 0 Solving 2 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 0 + -2 5x = 0 + -2 Combine like terms: 0 + -2 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4Solution
x = {0, -1, -0.4}
| 6k+10.5k=3K+12 | | K^2+2-3k=0 | | 7+49(2a+15)=-13 | | 2X+2y+z=72 | | 54=3x-30 | | 7+1(11)=P | | 7+1(X)=14 | | -11n-15n=8 | | -9(-5r-6+9m)= | | 7+1(2)=B | | -19=-0.5k | | 12-4x+9=0 | | (55-y)y=684 | | 6g+3g-10+3=47 | | -6x+5(-x+8)=139 | | 15(16)-14=c | | h+13.5=-13.5 | | 15(10)-14=c | | 15(2)-14=c | | 4x-9=4x+12 | | -8=3u-5 | | 10y-3y=7 | | (X+2)(x+10)=20 | | -2+9=1x+42 | | 7t+1+5t+8=162 | | -8v+3(v+8)=29 | | -45+15(x)=0 | | -45+15(0)=x | | 4x^3+10x^2-4x-10=0 | | y=-23000+4500x | | -7g=10-6g | | 3x-2y=4x |